If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(5m + -6) = 28 Reorder the terms: 2(-6 + 5m) = 28 (-6 * 2 + 5m * 2) = 28 (-12 + 10m) = 28 Solving -12 + 10m = 28 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '12' to each side of the equation. -12 + 12 + 10m = 28 + 12 Combine like terms: -12 + 12 = 0 0 + 10m = 28 + 12 10m = 28 + 12 Combine like terms: 28 + 12 = 40 10m = 40 Divide each side by '10'. m = 4 Simplifying m = 4
| p-3q=10 | | 3(2a+1)-4=11 | | 9v^2=-30v-25 | | 6x-5x=+1 | | 6w-14-9w=-5 | | 5-3*-1= | | 12y-3y+7=88 | | 8x^2+3x-7=0 | | 22p+11= | | 8(y+3)=2(2y+4) | | 4w^2+5=-21w | | 2(3)-5y=13 | | 7y=20 | | 3(x-2)+4x=8 | | 3x-10-5+6x=12 | | 4(7x-2)-16x= | | 7u=2u^2-4 | | z^2-13z+18=0 | | 5x(x-23)=-37 | | 20=4(d+3) | | (7+2a)+3a= | | 2-5y=13 | | 4(-3)+6(-8)+(-3)(78)-7(-42)= | | 6+x-x^2=0 | | n-12=5n+4 | | .4b+1=-11 | | 5x(x-23)=37 | | p+3p+2P=180 | | 12x^3+58x^2+70x= | | 13+(3xx)=50 | | x-2+x+x+5=40 | | 3w^2-11w=-6 |